Determinants of Domestic Violence in Women of Reproductive Age in Rwanda - Habyarimana, Faustin; Zewotir, Temesgen; Ramroop, Shaun (Journal of Economics and Behavioral Studies, 2018)
Domestic violence is a global public health problem. It is prevalent in both the developed world and developing countries. The objective of this study is to identify the factors that are associated with domestic violence against women of reproductive age in Rwanda. The data from the 2014/2015 Rwanda demographic and health survey were used. Generalized linear mixed model was used to account for random effects, overdispersion of residual and heterogeneity. The findings of this study revealed that wealth quintiles, education level of the husband or partner, polygamy, alcohol status of husband or partner, size of the family, number of sexual partners including the husband in the last 12 months, the province the victim lived in, the ownership of an asset in the form of a house or land and the societal attitude towards wife-beating, were the determinants of domestic violence in women of reproductive age. The findings of the risk factors in the current study can help the policy makers, public health workers and institutions in charge of gender monitoring in Rwanda to come up with effective strategies to reduce the domestic violence levels directed against women.